Molecular mechanisms involved in plant photoprotection - Pinnola, Alberta; Bassi, Roberto (Biochemical Society transactions, 2018)
Photosynthesis uses sunlight to convert water and carbon dioxide into biomass and oxygen. When in excess, light can be dangerous for the photosynthetic apparatus because it can cause photo-oxidative damage and decreases the efficiency of photosynthesis because of photoinhibition. Plants have evolved many photoprotective mechanisms in order to face reactive oxygen species production and thus avoid photoinhibition. These mechanisms include quenching of singlet and triplet excited states of chlorophyll, synthesis of antioxidant molecules and enzymes and repair processes for damaged photosystem II and photosystem I reaction centers. This review focuses on the mechanisms involved in photoprotection of chloroplasts through dissipation of energy absorbed in excess.